Tryptophan as a Central Hub for Host/Microbial Symbiosis. (May 2020) - Borghi, Monica; Puccetti, Matteo; Pariano, Marilena; Renga, Giorgia; Stincardini, Claudia; Ricci, Maurizio; Giovagnoli, Stefano; Costantini, Claudio; Romani, Luigina
Amino acid catabolism occurs during inflammation and regulates innate and adaptive immunity. The role of commensal bacteria in amino acid catabolism and the production of metabolites able to regulate the development and function of the innate immune system is increasingly being recognized. Therefore, commensal bacteria are key players in the maintenance of immune homeostasis. However, the intestinal microbiota also contributes to susceptibility and response to infectious diseases. This is self-evident for fungal infections known to occur as a consequence of weakened immune system and broad-spectrum antibiotic use or abuse. Thus, diseases caused by opportunistic fungi can no longer be viewed as dependent only on a weakened host but also on a disrupted microbiota. Based on these premises, the present review focuses on the role of amino acid metabolic pathways in the dialogue between the mammalian host and its microbiota and the potential implications in fungal commensalism and infectivity.